Role of Nepali Army from Nation Formation to Nation Building: People’s Perceptions - Paudel, Pushpa Raj (Unity Journal, 2022)
This paper has featured people’s beliefs and perceptions of the roles the national army has played in the formation of Nepal and nation building ever since its establishment in the eighteenth century by King Prithvi Narayan Shah, the chief architect of modern Nepal. This study has investigated and reported how the Nepali Army has contributed to developing the nation through its involvement in various development and construction works including the national pride projects besides its primary duty of the safeguarding of freedom and territorial integrity of the country. This study is qualitative in nature guided by interpretivism. Both primary and secondary sources of data have been used in the study. The data for this study came from interviews with purposively selected participants and reviews of various policy documents, books, journal articles, reports and websites of relevant ministries and organizations. The results revealed that the Nepali Army played a significant role in unifying Nepal which helped collect the energy to fight against external forces. Eventually, Nepal has been a sovereign nation since time immemorial. The national army has played an instrumental role in the development of Nepal through its involvement in the development works. It has ever helped citizenry coming to the front line at the times of crises. This paper argues that the Nepali Army needs to be more strategic for the safeguarding of the freedom and development of the country because of Nepal’s unique situatedness between two Asian rising powers– China and India. The Nepali Army, an efficient apparatus of the Government of Nepal, can further strengthen foreign relations with neighboring countries and beyond through effective military diplomacy.